Relationship between mind and brain: A proposal of solution based on forms of intra- and extra-individual negentropy - Alegre, Alberto A. (2015)
It is proposed that the problem of the mind-brain relationship can be overcome by a non-classical materialistic model of personality based on the information defined as a special form of negentropy with a structure and activity, which in five intra-individual categories, organizes all and each of the levels of the personality, and, in an extra-individual category organizes the society. This concept of information leads to a monistic view of the universe and turns into conceptions of society, personality, consciousness, and mental activity based on a theoretical framework that explains the nature of the social individual.